Archery injuries: A literature review - Agranovich, O. E.; Petrova, E. V.; Trofimova, S. I.; Sapogovskiy, A. V.; Melchenko, E. V.; Blagovechtchenski, E. D.; Afonichev, K. A. (Pediatric Traumology, Orthopaedics and Reconstructive Surgery, 2024)
BACKGROUND: Archery is one of the oldest human skills that survived to the present day. At first, it was used for hunting and war and later became a sport. The interest in archery has grown annually. Each type of sport has specific injuries. Information about archery-related injuries will allow us to develop preventive measures and help make this sport safer. The article will be useful for coaches, sports doctors, physiotherapists, and orthopedic surgeons.